GROWTH CHARACTERISTICS OF NEWLY ISOLATED INDONESIAN MICROALGAE UNDER DIFFERENT SALINITY - Wa Iba; Michael A. Rice; Lucie Maranda; Gary H. Wikfors (Indonesian Aquaculture Journal, 2018)
The aim of this study was to investigate the growth characteristics of microalgae strains isolated from Kendari Bay and the Wanggu River estuary, Indonesia. The growth of the isolates, denoted as Kb1-2, Kb1-3, Kb1-5, and Kb2-6, were evaluated under controlled conditions. A batch culture experiment of these strains except Kb2-6 was conducted for 15 days under salinity levels of 20, 25, 30 and 35 gL-1. Tetraselmis chui, Tisochrysis lutea and Chaetocero sneogracile were also culture and used as the growth references. Cell density was measured every day and cell size was measured from 50 live cells during the logarithmic phase. The cell sizes of three of the four Indonesian microalgae ranged from 1.2-11.8 µm, considered suitable for shrimp larvae. The Indonesian strains started the logarithmic phase of growth at all salinities tested from day 0 to day 3 after inoculation except for Kb1-3 that started the phase after a 3-day lag. Increased cell density over the culture period and division rate of Indonesian microalgae during the logarithmic phase of growth were similar at all salinities tested and similar to T. chui, Ti. lutea and C. neogracile. However, the final biomasses after 15 days of culture of all microalgal strains were affected by culture salinities tested. Indonesian microalgal strains showed similar dry weight and ash free dry weight to smaller-cell strains, Ti. lutea and C. neogracile. Indonesian strains (other than Kb2-6) are suggested as suitable live food candidates for mass culture in shrimp hatcheries based on their cell size, ability to survive long culture periods, and wide salinity tolerance.